ANALISIS PENGARUH MANAJEMEN RESIKO TERHADAP PERUBAHAN HARGA SAHAM PERDANA PADA INDUSTRI PERBANKAN DI BURSA EFEK INDONESIA - Hasnawati Hasnawati; Dion Caesar Nugroho (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2014)
Generally, the purpose of investors doing investment in a company is to get the high rcturn with the low risk The company that has the ability of good risk management can be said to perform well because they can minimize the risk to be faced by the banking industry. Investors are usually more interested in investing in companies that are expected to perform better because the stock prices of companies performing well will always increase. Preparation of this research aims to understand the influence of risk management (Interest-Rate Risk Credit Risk Solvency or Risk Capital Risk, - Hedging Strategy and Nature) to stock price changes on the banking industry in Indonesia. Data of this research is taken purposively based on sampling with the use of secondary data, such as the Indonesia Capital Market Directory (ICMD). The design used in this research is descriptive research method korelasional, with risk management as a independent variable and changes in stock prices as a dependent variable. At the end of this study can be drawn the conclusion that there is a difference in the partial results of the tests using an alpha level used. In the test using an alpha of 5% of all free variables are not significant to changes in stock prices, whereas the test using alpha 10%, solvency risk has a significant impact on stock price changes.